2013
DOI: 10.1016/j.biomaterials.2013.07.101
|View full text |Cite
|
Sign up to set email alerts
|

3D graphene oxide-encapsulated gold nanoparticles to detect neural stem cell differentiation

Abstract: Monitoring of stem cell differentiation and pluripotency is an important step for the practical use of stem cells in the field of regenerative medicine. Hence, a new non-destructive detection tool capable of in situ monitoring of stem cell differentiation is highly needed. In this study, we report a 3D graphene oxide-encapsulated gold nanoparticle that is very effective for the detection of the differentiation potential of neural stem cells (NSCs) based on surface-enhanced Raman spectroscopy (SERS). A new mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
109
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 43 publications
0
109
0
Order By: Relevance
“…A graphene–nanoparticle platform based on SERS detection was recently shown to be an effective and highly sensitive tool that could distinguish undifferentiated and differentiated stem cells, while maintaining cell viability. 245 In particular, GO-encapsulated AuNP films were generated on ITO surfaces, followed by use for the culture of mouse NSCs. On the basis of several reports, undifferentiated stem cells have been found to contain molecules bearing a high number of C=C bonds (high degree of saturation) as compared to differentiated cells.…”
Section: Cellular Interactions With Graphene–nanoparticle Hybrid Mmentioning
confidence: 99%
“…A graphene–nanoparticle platform based on SERS detection was recently shown to be an effective and highly sensitive tool that could distinguish undifferentiated and differentiated stem cells, while maintaining cell viability. 245 In particular, GO-encapsulated AuNP films were generated on ITO surfaces, followed by use for the culture of mouse NSCs. On the basis of several reports, undifferentiated stem cells have been found to contain molecules bearing a high number of C=C bonds (high degree of saturation) as compared to differentiated cells.…”
Section: Cellular Interactions With Graphene–nanoparticle Hybrid Mmentioning
confidence: 99%
“…We previously reported the electrical impedance characterization of human mesenchymal stem cell (hMSC) growth [29], hMSC differentiation into adipocytes [30], osteogenic differentiation of hMSCs [31], neural differentiation of hMSCs [32], adipose tissue-derived stem cell (ADSC) growth [33], and senescence of ADSCs [34]. Additionally, the effect of the electrode material and structure patterned by nanoparticles [35], graphene [36], or a mixture of nanoparticles and graphene [37] on stem cell differentiation was investigated. Our experiments in which we measured the electrochemical signals of differentiated or undifferentiated stem cells showed that the electrochemical signature can be used to quantify the pluripotency of the stem cells [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene-based nanomaterials, such as graphene oxide (GO), have recently gained considerable interest for tissue engineering applications due to their favorable chemical, electrical and mechanical properties. [9] Besides serving as a highly elastic and flexible structural reinforcement, substrates coated with GO have been demonstrated to promote the growth and differentiation of various stem cell lines including induced PSCs, MSCs and NSCs. [10] Based on these considerations, we demonstrate the use of GO as an effective coating material in combination with electrospun nanofibers for the selective differentiation of NSCs into oligodendrocytes.…”
mentioning
confidence: 99%